Inspecting the Accessibility of Chatbots and Mobile Banking for Emergent Users in the Context of People with Low Literacy - Melo, Giselle Lorrane Nobre (2024)
Digital banking services are embedded in people's daily lives. Despite this, these services are not accessible to everyone for various reasons, especially for people with low literacy. The objective of this work was to develop a method of accessibility inspection in mobile banking and banking chatbots, and the examination was directed toward the public mentioned before. For this reason, two inspection sequences were carried out on five Brazilian banking applications, mediated by accessibility considerations based on literature and case studies applied in the contexts of a riverside community and around elderly people with less experience in digital technology, as well as the mapping of design considerations with the Brazilian technical standard aimed at mobile applications and the investigation of banking chatbots made available by these applications. The results found in the inspections indicate how much the design considerations are satisfied, not satisfied and partially satisfied in the inspected applications and the comparison of the two inspections carried out. Additionally, it was possible to review and evaluate design considerations and propose improvements aimed at professionals who intend to develop accessible mobile bankings, as well as the importance of making banking chatbots.